KOH‐Enabled Axial‐Oxygen Coordinated Ni Single‐Atom Catalyst for Efficient Electrocatalytic CO2 Reduction. Issue 3 (5th January 2023) - Chen, Xuanyi; Liu, Wei; Sun, Yuxia; Tan, Ting; Du, Chen‐Xia; Li, Yuehui
Abstract: Precise control of the coordination structure of metal centers is an ideal approach to achieve reasonable selectivity, activity, and stability in the electrochemical reduction of CO2 . In this work, the KOH activation strategy for preparation of hierarchically porous material containing Ni single‐atoms with axial‐oxygen coordination is reported. Spectroscopic measurements reveal the multiple roles of KOH as oxygen source, pore‐making reagent and promoter for the formation of key phthalocyanine structure. It exhibits superior surface area (1801 m 2  g −1 ) and electrocatalytic performance (Faradaic efficiency of 94%, Turnover frequency of 11 362 h −1 ). Notably, KOH‐enabled architecture with abundant pores benefits the anchoring of Ni atoms and mass transfer for high activity and selectivity. Density functional theory calculations suggest that the axial‐oxygen ligand can promote the electronic delocalization of the Ni site for facilitating the *COOH formation and *CO desorption to efficiently produce CO. Abstract : Based on multirole KOH activation strategy, hierarchically porous Ni single‐atom catalysts with axial‐oxygen coordination are constructed. Detailed mechanistic study reveals the role of axial‐oxygen as an electronic modulator of Ni center, to facilitate the formation of *COOH intermediates and desorption of *CO.